Identification of the material properties of Al 2024 alloy by means of inverse analysis and indentation tests - Loo Chin Moy, Charles; Bocciarelli, M.; Ringer, S.; Ranzi, G. (Elsevier S.A., 2011)
This paper outlines an inverse analysis approach aimed at the identification of the mechanical properties of metallic materials based on the experimental results obtained from indentation tests. Previous work has shown the ill-posed nature of the inverse problem based on the load-penetration curve when dealing with mystical materials, which exhibit identical indentation curves even if possessing different yield and strain-hardening properties. For this reason, an additional measurement is used in the present study as input for the inverse analysis which consists of the maximum pile-up height measured after the indentation test. This approach lends itself for practical applications as the load-penetration curve can be easily obtained from commonly available micro-indenters while the pile-up present at the end of the test can be measured by different instruments depending on the size of the indented area, for example by means of an atomic force microscope or a laser profilometer. The inverse analysis procedure consists of a batch deterministic approach, and conventional optimization algorithms are employed for the minimization of the discrepancy norm. The first part of the paper outlines how the inclusion of both the maximum height of the pile-up and the indentation curve in the input data of the inverse analysis leads to a well-defined inverse problem using parameters of mystical materials. The approach is then applied to real experimental data obtained from three sets of 2024 Al alloy samples prepared using different age-hardening treatments. The accuracy of the identification process is validated against the mechanical properties obtained independently from standard tensile coupon tests. The reported results highlight the advantages of the proposed methodology in identifying the elastic modulus, yield stress and strain-hardening coefficient while minimizing the amount of information required to be collected from the experimental indentation tests.